Analysis of The Implementation of SCRUM in The Development of A BBLobster Content Management System - Sihombing, Denny Jean Cross; Ferdiando, Ferdiando (Journal of Information Systems and Informatics, 2023)
PT Rapier Technology International applies scrum in developing the BBLobster Content Management System (CMS). Scrum is a framework for developing an iterative, flexible, and effective BBLobster CMS designed to deliver significant value quickly. This study aims to identify the problems encountered in scrum implementation and validate the factors that influence the interaction with Scrum adoption during the BBLobster CMS development process using variable measurements. The measurement variables are the team factor variable, individual factor variable, technology factor variable, organizational factor variable, and scrum adoption variable. They analyzed the measurement of the data model (outer model) and structural model (inner model) using SmartPLS 3.0 after data collection using a questionnaire via google forms. The results of this study show that the analysis of the structural model test conducted by knowing the value of R-Square (R2) is a team factor variable, individual factor, technological factor, and organizational factor that has an influence of 67.4% on scrum adoption.